far east - Grigoryeva, Elena; Lidin, Konstantin (project baikal, 2020)
A little more than one and a half centuries ago, far eastern provinces became a part of Russia. A short but rich biography of this area remains poorly studied both by historians and theorists of architecture and urbanism. The capital of the Jewish autonomous region, Birobidzhan is a unique example of how to create a “promised land” for the Yiddish culture. As this culture vanishes, being replaced by the Hebrew culture around the world, Birobidzhan becomes more and more significant for the history of architecture. The article by A. Ivanova and A. Kovalevsky opens up the topic of vanishing cultural tradition of the Jewish people of the “late stage of the displacement period”. Such large cities of the region as Khabarovsk, Blagoveshchensk, Ussuriysk, Vladivostok are the topic for the articles based on field studies by M. Bazilevich and N. Kradin. Architecture of these Far Eastern cities reflects their wonderful history, a mixture of processes of industrialization of the area, mass migration and intersection of Western and Eastern cultures.